The Chinese version of the family accommodation scale for obsessive-compulsive disorder self-rated: reliability, validity, factor structure, and mediating effect - Liao, Zhenhua; Ding, Lijun; You, Ciping; Chen, Ying; Zhang, Wenchang (Frontiers in Psychiatry, 2022)
Background Family accommodation (FA) in obsessive compulsive disorder (OCD) is a common phenomenon. Based on the cost of training interviewers and the time required to administer the scale, the Family Accommodation Scale for Obsessive-Compulsive Disorder Interviewer-Rated (FAS-IR) has been restricted to specific settings. A self-rated version of the family accommodation scale may solve these problems. The aim of this study was to examine the reliability, validity and factor structure of the Family Accommodation Scale Self-rated version (FAS-SR), and the relationship among FA, symptom severity and functional impairment. Methods In total, 171 patients with OCD and 145 paired relatives participated in this study. The Sheehan Disability Scale (SDS), Obsessive-Compulsive Inventory Revised (OCI-R), Zung Self-Rating Depression Scale (Zung-SDS), 12-item Family Assessment Devices (FAD-12), Clinical Global Impression of Severity Scale (CGI-S), Global Assessment of Functioning (GAF), and Yale-Brown Obsessive-Compulsive Scale (Y-BOCS) were used as tools for patients. The FAS-SR, FAS-IR, FAD-12, and the patients’ symptom severity of Y-BOCS compulsion were used as tools for relatives. The psychometric properties of the FAS-SR were evaluated using Cronbach’s alpha coefficient, test-retest reliability and validity. Mediation analysis was used to determine the relationship among FA, symptom severity and functional impairment. Results A total of 97.9% of relatives of OCD patients reported at least one kind of FA behavior, and 56.6% of participants engaged in FA every day in the past week. The FAS-SR includes a three-factor structure: (1) providing reassurance and participation; (2) facilitation; and (3) modification. The scale’s Cronbach’s alpha and test-retest coefficients were 0.875 and 0.970, respectively. The total FAS-SR score was significantly positively associated with the Y-BOCS, FAD-12, CGI-S, FAS-IR, and SDS scores, and negatively associated with the total GAF score. FA partially mediated the relationship between symptom severity and functional impairment. Conclusions The FAS-SR was proven to have satisfactory psychometric properties, and can play an important role in the evaluation and early intervention of OCD. This result indicates the importance of assessing symptom severity in conjunction with FA when evaluating OCD patients’ functional impairment.